Indigenous and Minority Populations Perspectives From Scholars and Writers across the World - Gbendazhi Barnabas, Sylvanus (IntechOpen, 2023)
The sections and chapters contained in this book deal with issues and challenges facing indigenous and minority populations located in several geographical areas of the world. The papers are written by writers and scholars from various parts of the world and, like any piece of literature on indigenous and minority populations, the topics are diverse. The perspectives are both interdisciplinary and multi-disciplinary. The issues examined in the various chapters cover areas pertaining to their human rights, preservation of their culture and identity, traditional knowledge, and their challenges, but also scholarly and epistemological approaches to understanding and articulating such topics in academic contexts. Indeed, the issues around indigenous and minority populations across the world transcend their human rights concerns in relation to dominant groups and institutions within the territorial boundaries of the modern states where they currently live. These issues are cultural, anthropological, sociological, philosophical and epistemological, as well as historical. Any scholarly piece of work on indigenous and minority populations is therefore inevitably inter-disciplinary, multi-disciplinary or both. The various topics examined by the authors epitomize this diversity of issues around such populations. The book is a significant source of information for students, academics, practitioners, policymakers, government officials and non-governmental organisations working on issues that pertain to such populations at national, regional and global levels.